2003
DOI: 10.1177/00238309030460020901
|View full text |Cite
|
Sign up to set email alerts
|

Early Word Learners' Ability to Access Phonetic Detail in Well-Known Words

Abstract: Several recent studies from our laboratory have shown that 14-month-old infants have difficulty learning to associate two phonetically similar new words to two different objects when tested in the Switch task. Because the infants can discriminate the same phonetic detail that they fail to use in the associative word-learning situation, we have argued that this word-learning failure results from a processing overload. Here we explore how infants perform in the Switch task with already known minimally different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
193
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(210 citation statements)
references
References 36 publications
16
193
1
Order By: Relevance
“…Research by Gerken et al (2015) suggests that storing two stimulus dimensions is more demanding on infant pattern learning than storing a single dimension. Task demands are also known to impact word learning (Fennell & Werker, 2003;Yoshida et al, 2009). Rost and McMurray (2009) have called task complexity into question as a full explanation of 14-month-olds' word learning performance in the Switch paradigm, since increasing talker variability, which presumably increases task complexity, actually improves word learning.…”
Section: Implications Of the Results For Our Understanding Of Early Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Gerken et al (2015) suggests that storing two stimulus dimensions is more demanding on infant pattern learning than storing a single dimension. Task demands are also known to impact word learning (Fennell & Werker, 2003;Yoshida et al, 2009). Rost and McMurray (2009) have called task complexity into question as a full explanation of 14-month-olds' word learning performance in the Switch paradigm, since increasing talker variability, which presumably increases task complexity, actually improves word learning.…”
Section: Implications Of the Results For Our Understanding Of Early Wmentioning
confidence: 99%
“…Moving objects are commonly used in the Switch paradigm (e.g., Fennell & Werker, 2003). However, it is possible that the use of looming videos here increased the task complexity relative to the task used by Rost and McMurray (2009;.…”
Section: Experimental Designmentioning
confidence: 99%
“…If, for example, the procedure of Stager and Werker (1997, Experiment 2) were not sensitive to subtle differences in the degree to which words are activated, MP effects would not be found. This alternative would be excluded if children in the same procedure did show MP effects on known words; studies of this sort are in progress (see Fennell & Werker, 2003, for a step in this direction).…”
Section: Discussionmentioning
confidence: 99%
“…As a series of elegant studies has shown, the underlying discrimination ability persists, even as task demands determine whether infants can make this ability manifest or not (Fennell & Werker, 2003;Stager & Werker, 1997;Yoshida, Fennell, Swingley, & Werker, 2009). What was a simple discrimination task for an 8-month-old is construed as a wordlearning task by a 14-month-old because the child's relation to the task has changed in a qualitative way; the older child's attention is now focused on creating new mappings.…”
Section: U-shaped Developmental Trajectoriesmentioning
confidence: 99%